Satintelkam Efforts Through Intelligence Raising for Control of Community Organizational Activities in the Jurisdiction of the Magelang Police Region - Putra, Daffa Raissa (Police Studies Review, 2024)
The activities of community organization in Mafelang Regency such as demonstrations and conflicts between community organization have had a huge impact on the security conditions in the area. The security intelligence unit of the Magelang Police as the agency responsible for the activities of community organization has an important role in controlling the activities of community organization in Magelang. security intelligence unit, especially the socio-cultural unit, has been raising intelligence in controlling the activities of mass organizations that can disrupt security, but the raising has not been carried out properly due to various problems, such as the absence of special information products and main elements of description. The method used is a qualitative approach and focuses on problems related to security intelligence unit efforts. Sources of data obtained through interviews, observations, and document review from the security intelligence unit and other agencies as well as the community organization. Validity is carried out on each data obtained and analyze the data to obtain conclusions. The concepts used include the concept of effort, the basic concept of intelligence, the basic concept of raising intelligence, and the concept of community organization. The theory used is the 6M management element and the MOTL theory. Intelligence-gathering efforts carried out by the security intelligence unit against community organizations have not been carried out properly due to several problems. These problems include personnel, budget, facilities and infrastructure, intelligence products, fundraising targets, and the implementation of the fundraising method according to the standard operating procedures (SOP) used. Through factual conditions, the author analyzes the ideal conditions to get a solution to the problem. Through these discussions, security intelligence unit needs to improve organizational resources so that they can be maximized and the methods of raising are in accordance with applicable rules and SOP.